The role of social capital and networks in the integration and implementation of health and human rights programmes amongst civil society organizations in Cape Town South Africa - Nefdt, Wendy (Department of Public Health and Family Medicine, 2024)
Civil society organisations are lauded as being key stakeholders for the promotion of health and human rights in society. They are well positioned to engage with communities to address growing inequalities such access to health care, increasing violation of health and human rights, poverty and unemployment in communities. In order to build agency for the attainment of the highest attainable standard of health conducive to living a life in dignity, civil society organizations are encouraged to work in collaboration with each other and with health system decision makers in the development of rights-based policies and programmes. The research study was located within a Learning Network for Health and Human Rights in the Faculty of Social Sciences at the University of Cape Town. The Learning Network is an ensemble of various civil society organizations and academic partners, conceptualized for the purpose of building agency amongst civil society organizations to realize health and human rights programmes. The research study explored the role of social capital and social networks as vehicles for building agency within civil society organisations. The study questioned whether and how the agency that was developed through participation in the Learning Network co-learning and co-research activities, enabled civil society organizations to integrate and implement health and human rights programmes in communities. Through a process of qualitative case study methodologies using Semi-Structured Interviews with 13 participants, Focus Group Discussions with three groups of civil society beneficiaries and an extensive Documentary Analysis of the Learning Network documents over the period 2010-2017, the findings of the study show that social capital developed through the Learning Network for Health and Human Rights built agency for action amongst its members. The qualitative methodology of Participatory Action Research utilized in the Learning Network , provided an enabling platform for reflection and review of the activities and relationships in the group. Aspects of social capital such as trust amongst the members were addressed within this enabling platform.